Construction of a high density genetic linkage map to define the locus conferring seedlessness from Mukaku Kishu mandarin - Kumar, Krishan; Yu, Qibin; Bhatia, Dharminder; Honsho, Chitose; Gmitter, Frederick G. (Frontiers in Plant Science, 2023)
Mukaku Kishu (‘MK’), a small sized mandarin, is an important source of seedlessness in citrus breeding. Identification and mapping the gene (s) governing ‘MK’ seedlessness will expedite seedless cultivar development. In this study, two ‘MK’-derived mapping populations- LB8-9 Sugar Belle® (‘SB’) × ‘MK’ (N=97) and Daisy (‘D’) × ‘MK’ (N=68) were genotyped using an Axiom_Citrus56 Array encompassing 58,433 SNP probe sets, and population specific male and female parent linkage maps were constructed. The parental maps of each population were integrated to produce sub-composite maps, which were further merged to develop a consensus linkage map. All the parental maps (except ‘MK_D’) had nine major linkage groups, and contained 930 (‘SB’), 810 (‘MK_SB’), 776 (‘D’) and 707 (‘MK_D’) SNPs. The linkage maps displayed 96.9 (‘MK_D’) to 98.5% (‘SB’) chromosomal synteny with the reference Clementine genome. The consensus map was comprised of 2588 markers including a phenotypic seedless (SFs)-locus and spanned a genetic distance of 1406.84 cM, with an average marker distance of 0.54 cM, which is substantially lower than the reference Clementine map. For the phenotypic SFs-locus, the distribution of seedy and seedless progenies in both ‘SB’ × ‘MK’ (55:42, χ2 =1.74) and ‘D’ × ‘MK’ populations (33:35, χ2 =0.06) followed a test cross pattern. The SFs-locus mapped on chromosome 5 with SNP marker ‘AX-160417325’ at 7.4 cM in ‘MK_SB’ map and between two SNP markers ‘AX-160536283’ and ‘AX-160906995’ at a distance of 2.4 and 4.9 cM, respectively in ‘MK_D’ map. The SNPs ‘AX-160417325’ and ‘AX-160536283’ correctly predicted seedlessness of 25-91.9% progenies in this study. Based on the alignment of flanking SNP markers to the Clementine reference genome, the candidate gene for seedlessness hovered in a ⁓ 6.0 Mb region between 3.97 Mb (AX-160906995) to 10.00 Mb (AX-160536283). This region has 131 genes of which 13 genes (belonging to seven gene families) reportedly express in seed coat or developing embryo. The findings of the study will prove helpful in directing future research for fine mapping this region and eventually underpinning the exact causative gene governing seedlessness in ‘MK’.